Contextualized Tirakat Form to Christian Spiritual Formation among Javanese - Harwanto, Budi (Klabat Theological Review, 2020)
Tirakat is an important part in Javanese culture. It points to a spiritual path in a sense of a method of a spiritual practice. The ways of tirakat have been an element of the culture for centuries. It is for this situation that evangelizing and nurturing newly non-Christian Javanese converted have been a challenge for Adventist ministry. This research attempts to seek an answer of the church which is expected to find some strategies for nurturing the members from Javanese culture background. The new converts are isolated from their background and stay in a new culture in the church. Consequently, some of the new members cannot survive in the new culture, custom, and rituals. This study addresses the issue of contextualized tirakat form to spiritual formation as a part of discipling new members in the local church. An analysis of both theological-biblical and cultural practice indicates that some elements of the tirakat ritual are strongly correlated with the Christian spiritual formation. The tirakat form can be contextualized in the spiritual formation form to experience spiritual growth. By giving a new meaning and modified form the believers are able to keep the tirakat ritual based on the Scriptures teaching. An evaluation of tirakat practice found some positive elements which can be continued to the form of Christian formation. However, the negative aspects need functional substitutes or discontinued. Through the worldview transformation the tirakat form as spiritual formation activity will lead the Javanese congregation to have good spiritual growth, strong faith, and ability to involve in the church mission and ministry. Keywords: tirakat; discipleship; spiritual formation; Javanese congregation